Sleep-Disordered Breathing, Quality of Sleep and Chronotype in a Cohort of Adult Patients with Bardet–Biedl Syndrome - Dormegny L (Dove Medical Press, 2021)
Léa Dormegny,1,2 Reana Velizarova,1 Carmen M Schroder,1,3 Ulker Kilic-Huck,1,3 Henri Comtet,1,3 Hélène Dollfus,4 Patrice Bourgin,1,3 Elisabeth Ruppert1,3 1Centre des Troubles du Sommeil - CIRCSom, Hôpital Civil, University of Strasbourg, Strasbourg, 67091, France; 2Department of Ophthalmology, Hôpital Civil, University of Strasbourg, Strasbourg, 67091, France; 3Institute for Cellular and Integrative Neurosciences, CNRS - UPR 3212, Strasbourg, 67000, France; 4Centre des Affections Rares en Génétique Ophtalmologique (CARGO), University of Strasbourg, Strasbourg, 67091, FranceCorrespondence: Elisabeth RuppertCentre des Troubles du Sommeil - CIRCSom - Hôpital Civil, 1, place de l’Hôpital, BP 426, Cedex, Strasbourg, 67091, FranceTel +33 3 88 11 64 30Fax +33 3 88 11 51 53Email elisabeth.ruppert@chru-strasbourg.frObjective/Background: Bardet–Biedl syndrome (BBS) is a rare but well-recognized ciliopathy with high genetic and phenotypic heterogeneity. Cardinal features include obesity, diabetes and high blood pressure (HBP), which are often associated with sleep-disordered breathing. Also, the high prevalence of blindness due to retinal dystrophy could affect circadian sleep–wake rhythms. We characterized in this cohort of adult BBS patients sleep-disordered breathing, sleep quality, daytime sleepiness and chronotype.Patients and Methods: Thirty-two patients with genetically confirmed BBS were included in this observational single center study. Overnight respiratory polygraphy was performed for sleep apnea syndrome (SAS) in 30 patients. Quality of sleep, daytime sleepiness, fatigue and chronotype were assessed in 25 patients using Pittsburgh sleep quality index (PSQI), 14-day sleep diary (SD), Epworth sleepiness scale (ESS), Pichot fatigue scale (PFS) and Horne and Ostberg morningness-eveningness questionnaire (MEQ).Results: Patients’ mean age was 32± 11 years and mean BMI 32.6± 7.7 kg/m2. Eleven (35%) patients had HBP and 7 (22%) diabetes. Moderate to severe sleep apnea syndrome (SAS) was present in 5 (17%) and was not associated with altered sleep, daytime sleepiness or fatigue. Most of the patients (63%) evaluated their sleep as of good quality (PSQI ≤ 5). Median scores of sleep quality, daytime sleepiness and fatigue were normal (PSQI of 3.0 [2.0– 6.0], ESS of 9.0 [6.0– 13.0] and PFS of 8.0 [3.0– 13.0], respectively). Predominant chronotypes according to MEQ were either “intermediate” (57%) or “moderate morning” (29%). None had a free running sleep–wake cycle. 14-day SD revealed overall few awakenings at night and low daytime napping.Conclusions: Given the cardiovascular risk factors, systematic screening for SAS should be considered in BBS patients, regardless of sleep and daytime vigilance complaints. None of these highly visually impaired patients had a circadian sleep–wake rhythm disorder. Further objective assessments are needed to better characterize sleep and circadian rhythms in BBS patients.Keywords: Bardet–Biedl syndrome, ciliopathy, sleep disordered breathing, sleep apnea syndrome, chronotype, circadian rhythm sleep wake disorder